Why and how has the United Kingdom become a high producer of health inequalities research over the past 50 years? A realist explanatory case study - Lucinda Cash-Gibson; Eliana Martinez-Herrera; Joan Benach (BMC, 2023)
Abstract Background Evidence on health inequalities has been growing over the past few decades, yet the capacity to produce research on health inequalities varies between countries worldwide and needs to be strengthened. More in-depth understanding of the sociohistorical, political and institutional processes that enable this type of research and related research capacity to be generated in different contexts is needed. A recent bibliometric analysis of the health inequalities research field found inequalities in the global production of this type of research. It also found the United Kingdom to be the second-highest global contributor to this research field after the United States. This study aims to understand why and how the United Kingdom, as an example of a "high producer" of health inequalities research, has been able to generate so much health inequalities research over the past five decades, and which main mechanisms might have been involved in generating this specific research capacity over time. Methods We conducted a realist explanatory case study, which included 12 semi-structured interviews, to test six theoretical mechanisms that we proposed might have been involved in this process. Data from the interviews and grey and scientific literature were triangulated to inform our findings. Results We found evidence to suggest that at least four of our proposed mechanisms have been activated by certain conditions and have contributed to the health inequalities research production process in the United Kingdom over the past 50 years. Limited evidence suggests that two new mechanisms might have potentially also been at play. Conclusions Valuable learning can be established from this case study, which explores the United Kingdom's experience in developing a strong national health inequalities research tradition, and the potential mechanisms involved in this process. More research is needed to explore additional facilitating and inhibiting mechanisms and other factors involved in this process in this context, as well as in other settings where less health inequalities research has been produced. This type of in-depth knowledge could be used to guide the development of new health inequalities research capacity-strengthening strategies and support the development of novel approaches and solutions aiming to tackle health inequalities.